Using virtual reality to train designers to develop friendly interfaces for achromatic vision patients - Constantinou, Vaso; Lanitis, Andreas; Ioannou, Andri (My University, 2017)
An investigation in the use of Virtual Reality as a means of training designers to design interfaces accessible to achromatic vision patients is presented. Within this context virtual environments incorporating real life environments are visualised through the eyes of achromatic vision patients and designers are given the opportunity to navigate and interact with the virtual environment using different types of interaction schemes. Through the process designers assess the applicability of different interaction methods adjusted to the needs of achromatic vision patients. According to the results of an experimental investigation, the idea of using Virtual Reality-based training is deemed effective.
Keywords: Accessibility; Achomatic vision; Deuteranopia; Protanopia; Tritanopia; Virtual reality